Absorption coefficient for nanosecond laser pulse in porous material. (16th October 2015) - Gus'kov, S Yu; Cipriani, M; De Angelis, R; Consoli, F; Rupasov, A A; Andreoli, P; Cristofari, G; Di Giorgio, G
Abstract: The absorption of powerful laser radiation in a porous material is investigated theoretically and numerically. The behavior of the medium during the process of pores filling in the heated region is described by a model of viscous homogenization. The porous material is described as a partially homogenized plasma where the density within the pores increases with time from zero to an average density of the porous substance depending on the ratio of laser pulse duration and homogenization time. An expression describing the time and space dependence of the absorption coefficient of laser radiation in such a material is derived. The initial pore's sizes, the average density of the material and the laser intensity are the parameters of the model. The absorption of a nanosecond laser pulse in totally ionized plasma of porous material of light elements is investigated numerically within the present model. The calculations are performed for porous media with an average density larger or smaller than the critical density of the laser-produced plasma. For the latter, the results are compared with those for a homogeneous plasma with the same density.